Bone cement with antibacterial activity and preparation method thereof
By preparing nanofibers with glycerol laurate and PMMA copolymer and using them in bone cement, the problem of enhanced bacterial resistance caused by existing antibiotic bone cement is solved, and efficient antibacterial effect is achieved and the mechanical properties of bone cement is maintained.
Patent Information
- Application Number
- CN202411909090.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-28
AI Technical Summary
The existing antibiotic bone cement can easily lead to increased bacterial resistance during use, and nanoparticles are toxic to the human body as antibacterial agents, which limits their application.
Nanofibers were prepared by electrospinning using glycerol laurate and PMMA copolymer. As antibacterial substances for bone cement, the antibacterial properties of bone cement were improved through the porous structure of nanofibers.
It is achieved that the antibacterial properties of bone cement is significantly improved without damaging the mechanical properties of bone cement, and the release efficiency of antibacterial substances is improved.
Smart Images

Figure CN119701081A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of biomedical materials, and in particular to a bone cement with antibacterial properties and a preparation method thereof. Background Art
[0002] In order to better prevent or treat infected bone defects, antibiotic bone cement is generally used to fill bone defects to control infection. However, due to the irrational use of antibiotics, adverse reactions often occur, resulting in increased bacterial resistance and even treatment failure.
[0003] The release of a large amount of effective antibacterial agents in bone cement is crucial for the effective treatment of infection. Currently, metal nanoparticles are used as bone cement antibacterial agents. Although they have strong antibacterial activity and non-specific targets, they are toxic and harmful to the human body, which limits their application.
[0004] In view of this, the present invention is proposed. Summary of the invention
[0005] One of the purposes of the present invention is to provide a bone cement with antibacterial properties, which has good antibacterial properties and mechanical properties.
[0006] A second object of the present invention is to provide a method for preparing bone cement with antibacterial properties.
[0007] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0008] In a first aspect, a bone cement with antibacterial properties is provided, comprising a solid phase component and a liquid phase component; the solid phase component comprises, by mass percentage, 70-78% of PMMA, 1.5-2.0% of an initiator, 12-16% of lauric acid glyceryl ester-PMMA nanofibers, and 8-12% of a developer;
[0009] The liquid phase components include, by mass concentration, 98-99% of MMA, 1.0-2.0% of accelerator, and 100±10ppm of inhibitor.
[0010] Furthermore, the diameter of the laurin-PMMA nanofiber is 200nm-600nm; the diameter of the pores on the surface of the laurin-PMMA nanofiber is 10-50nm.
[0011] Furthermore, the preparation method of the lauric acid glyceryl ester-PMMA nanofibers comprises:
[0012] The mixed solution of lauric acid glyceryl ester and PMMA copolymer was electrospun to form fibers.
[0013] Furthermore, the laurin includes at least one of monolaurin and dilaurin.
[0014] In a second aspect, a method for preparing the antibacterial bone cement is provided, comprising the following steps:
[0015] (a) providing laurin-PMMA nanofibers;
[0016] (b) chopping the lauric acid glyceryl ester-PMMA nanofibers and mixing them with PMMA, an initiator and a developer to obtain a solid phase component;
[0017] (c) mixing MMA, a promoter and an inhibitor to obtain a liquid phase component;
[0018] (d) The solid phase component and the liquid phase component constitute the bone cement with antibacterial properties.
[0019] Furthermore, the preparation method of laurin-PMMA nanofibers in step (a) comprises:
[0020] The mixed solution of lauric acid glyceryl ester and PMMA copolymer was electrospun to form fibers.
[0021] Further, the mass ratio of lauric acid glyceryl and PMMA copolymer in the mixed solution of lauric acid glyceryl and PMMA copolymer is 0.5-1:1;
[0022] Preferably, the number average molecular weight of PMMA polymer is 1×10 5 -5×10 5 .
[0023] Further, the solvent used for the mixed solution of lauric acid glyceryl ester and PMMA copolymer is a mixed solvent of dichloromethane and trifluoroacetic acid;
[0024] Preferably, the volume ratio of dichloromethane to trifluoroacetic acid is 2:1-2.
[0025] Furthermore, the total concentration of laurin and PMMA copolymer in the mixed solution of laurin and PMMA copolymer is 15-20 wt %.
[0026] Furthermore, the process parameters of electrospinning include at least one of the following conditions:
[0027] Spinning voltage: 15-20kv;
[0028] Spinning speed: 1.5-2ml / h;
[0029] Spinning distance: 9-13cm;
[0030] Receiving substrate: PET.
[0031] The antibacterial bone cement and preparation method thereof provided by the present invention have at least the following beneficial effects:
[0032] The invention adopts laurin as the antibacterial substance of bone cement, and composites it with PMMA copolymer to prepare nanofibers. Laurin is made into nanofiber structure. The porous structure on the surface of nanofiber can improve the antibacterial performance of bone cement.
[0033] The present invention can ensure that the mechanical properties of bone cement remain unchanged while increasing the amount of antibacterial substance added.
[0034] Preferably, the composite nanofibers are prepared by electrospinning. The obtained nanofibers have a large specific surface area and nano-voids on the surface, which improve the dispersibility and deposition rate of the drug in the bone cement, thereby increasing the drug release amount. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0036] Figure 1 This is a morphology image of the lauric acid glyceryl ester-PMMA nanofibers prepared in Example 1;
[0037] Figure 2 This is the test result of bone cement antibacterial rate in Experimental Example 1. DETAILED DESCRIPTION
[0038] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0039] According to the first aspect of the present invention, a bone cement with antibacterial properties is provided, comprising a solid phase component and a liquid phase component; the solid phase component comprises, in terms of mass percentage, 70-78% PMMA, 1.5-2.0% initiator, 12-16% laurin-PMMA nanofibers and 8-12% developer; the liquid phase component comprises, in terms of mass concentration, 98-99% MMA, 1.0-2.0% accelerator and 100±10ppm inhibitor.
[0040] Solid phase components
[0041] Based on the solid phase component (100%), typical but non-limiting mass percentages of polymethyl methacrylate (PMMA copolymer) are, for example, 70%, 71%, 72%, 73%, 74%, 75%, 76%, 77%, and 78%.
[0042] Initiators include, but are not limited to, benzoyl peroxide (BPO).
[0043] A typical but non-limiting mass percentage of the initiator based on the solid phase component (100%) is, for example, 1.5%, 1.6%, 1.7%, 1.8%, 1.9% or 2%.
[0044] Initiators are used to initiate the reaction of PMMA and MMA.
[0045] “Lauryl glycerol-PMMA nanofibers” refer to nanofibers prepared by blending lauric acid glycerol and PMMA copolymer.
[0046] Lauric acid glyceride includes but is not limited to at least one of monolaurin and dilaurin. Lauric acid glyceride oils and fats are derived from purified or unpurified palm kernel oil, palm kernel olein, palm kernel solid oil, coconut oil, ester exchange oils of these oils and fats, and mixed oils containing more than one of these oils and fats.
[0047] Among them, glyceryl monolaurate (Glycerol Monolaurate, referred to as GML) is also known as lauric acid monoglyceride, is an excellent food emulsifier, HLB value is 5.2, is also a safe, efficient, broad-spectrum antibacterial agent, naturally present in breast milk, coconut oil and American palm, can also be derived from natural oils and lauric acid and glycerol direct esterification obtained, its structure and function are exactly the same as the natural existence. The U.S. Food and Drug Administration (FDA) approved GML as GRAS (generally recognized as safe) food emulsifier (21CFR GRAS182.4505) in 1977. my country's Ministry of Health also approved its application in food in 2005, and stipulated that it can be added in food according to actual production needs. In 2011, GML was incorporated into mono- and di-fatty acid glycerides in GB2760.
[0048] PMMA copolymer is consistent with the main component of bone cement.
[0049] There is no limitation on the method for forming the nanofibers, and the nanofibers can be prepared using existing methods.
[0050] As a preferred embodiment, the method for preparing laurin-PMMA nanofibers comprises: electrospinning a mixed solution of laurin and PMMA copolymer to form fibers.
[0051] Electrospinning technology is a spinning method in which a polymer solution or melt is sprayed and stretched under the action of electrostatics to obtain nano-scale fibers.
[0052] Preferably, the diameter of the laurin-PMMA nanofibers prepared by the electrospinning technology of the present invention is 200nm-600nm; the diameter of the pores on the surface of the laurin-PMMA nanofibers is 10-50nm.
[0053] Typical but non-limiting diameters of the laurin-PMMA nanofibers are, for example, 200 nm, 250 nm, 300 nm, 350 nm, 400 nm, 450 nm, 500 nm, 550 nm, 600 nm.
[0054] Principle: Laurin has a good inhibitory effect on both Gram-positive and Gram-negative bacteria.
[0055] Lauric acid glyceryl ester is an ester-type antibacterial agent with a hydrophilic group and a hydrophobic group that is easily soluble in biological membranes. Its antibacterial mechanism is mainly achieved by affecting bacterial cell walls, cell membranes, metabolic enzymes, protein synthesis systems and other cell substructures.
[0056] Based on the solid phase component (100%), a typical but non-limiting mass percentage of laurin-PMMA nanofibers is, for example, 12%, 13%, 14%, 15%, or 16%.
[0057] Developers include, but are not limited to, barium sulfate or zirconium oxide.
[0058] Based on the solid phase component (100%), typical but non-limiting mass percentages of the developer are, for example, 8%, 9%, 10%, 11%, and 12%.
[0059] Contrast dye is used to facilitate visualization during surgery.
[0060] Liquid components
[0061] Based on the liquid phase component (100%), a typical but non-limiting mass concentration of methyl methacrylate monomer (MMA) is, for example, 98.0%, 98.5%, or 99.0%.
[0062] The accelerator includes, but is not limited to, N,N-dimethyl-p-toluidine DMPT.
[0063] Based on the liquid component (100%), a typical but non-limiting mass concentration of the promoter is, for example, 1.0%, 1.5% or 2.0%.
[0064] Used to promote the polymerization process of bone cement.
[0065] The polymerization inhibitor includes, but is not limited to, hydroquinone HQ.
[0066] A typical but non-limiting mass concentration of the polymerization inhibitor is, for example, 90 ppm, 95 ppm, 100 ppm, 105 ppm or 110 ppm based on the liquid phase component (100%).
[0067] Used to prevent methyl methacrylate from self-polymerization in the liquid phase component.
[0068] Preferably, the liquid-to-solid ratio of the liquid phase component to the solid phase component in the bone cement is 1 (ml):2-2.1 (g).
[0069] The present invention adopts laurin as an antibacterial substance, and blends it with a PMMA copolymer to prepare nanofibers, and laurin is made into a nanofiber structure. The porous structure on the surface of the nanofiber can improve the antibacterial performance of bone cement. The present invention can ensure that the mechanical properties of bone cement remain unchanged while increasing the amount of antibacterial substance added.
[0070] According to a second aspect of the present invention, there is provided a method for preparing the above-mentioned antibacterial bone cement, comprising the following steps:
[0071] (a) providing laurin-PMMA nanofibers;
[0072] (b) chopping the lauric acid glyceryl ester-PMMA nanofibers and mixing them with PMMA, an initiator and a developer to obtain a solid phase component;
[0073] (c) mixing MMA, a promoter and an inhibitor to obtain a liquid phase component;
[0074] (d) The solid phase component and the liquid phase component constitute the bone cement with antibacterial properties.
[0075] The descriptions about laurin-PMMA nanofibers, PMMA, initiator, developer, MMA, promoter and inhibitor are the same as the corresponding descriptions in the first aspect and will not be repeated here.
[0076] In a preferred embodiment, the method for preparing laurin-PMMA nanofibers in step (a) comprises: electrospinning a mixed solution of laurin and PMMA copolymer to form fibers.
[0077] The electrospinning process specifically includes:
[0078] Spinning solution: laurin and PMMA copolymer (m / m=0.5-1:1) are dissolved in a mixed solution of dichloromethane / trifluoroacetic acid (v / v=2:1-2).
[0079] Solution concentration: the total concentration of laurin and PMMA copolymer in the spinning solution is 15-20 wt%, for example, 15%, 16%, 17%, 18%, 19% or 20%.
[0080] Preferably, the electrospinning process parameters include:
[0081] Spinning voltage: 15-20kv, such as 15kv, 16kv, 17kv, 18kv, 19kv, 20kv;
[0082] Spinning speed: 1.5-2 ml / h, for example, 1.5 ml / h, 1.6 ml / h, 1.7 ml / h, 1.8 ml / h, 1.9 ml / h, 2 ml / h;
[0083] Spinning distance: 9-13cm, for example 9cm, 10cm, 11cm, 12cm, 13cm;
[0084] Receiving substrate: PET.
[0085] Spinning results: The diameter of the obtained nanofibers is between 200nm and 600nm, and there are many tiny holes on the fiber surface, which are conducive to the release of antibacterial substances.
[0086] A typical method for preparing bone cement comprises the following steps:
[0087] Electrospinning process of nanofibers: Spinning solution: lauric acid glyceryl ester and PMMA copolymer (0.5-1; 1) were dissolved in a mixed solution of dichloromethane / trifluoroacetic acid (2:1-2).
[0088] Solution concentration: 15-20%;
[0089] Spinning voltage: 15-20kv;
[0090] Spinning speed: 1.5-2ml / h;
[0091] Spinning distance: 9-13cm;
[0092] Receiving substrate: PET.
[0093] Spinning results: The diameter of the obtained nanofibers is between 200nm and 600nm, and there are many tiny holes on the fiber surface, which are conducive to the release of antibacterial substances.
[0094] Bone cement formula: The obtained nanofibers are cut into pieces and mixed with bone cement powder, and then mixed with bone cement liquid to prepare bone cement.
[0095] Powder: PMMA: 70-78%;
[0096] BPO: 1.5-2.0%;
[0097] Monolaurin-PMMA nanofibers: 12-16%;
[0098] BaSO4: 8-12%;
[0099] Liquid: MMA: 98-99%;
[0100] DMPT: 1.0-2.0%;
[0101] HQ: 100±10ppm ;
[0102] It should be noted that bone cement is sold as a set of solid and liquid components. When used, the solid and liquid components are mixed (blended) to form a dough or toothpaste state, and then filled into the human body before fully solidified.
[0103] The present invention is further described below by way of examples. Unless otherwise specified, the materials in the examples are prepared according to existing methods or directly purchased from the market.
[0104] Example 1 Preparation of lauric acid glyceryl ester-PMMA nanofibers
[0105] 5g of lauric acid glyceride and 10g of PMMA powder (0.5:1) were added to a mixed solvent of 78.75g of dichloromethane and trifluoroacetic acid (v / v=2:1) to prepare a spinning solution with a concentration of 16wt%, which was heated and magnetically stirred for 24h. When it was completely dissolved and a uniform solution was obtained, it was transferred to a 100ml syringe, and an XXG spinning needle was selected to connect the syringe, which was fixed on the electrospinning device, and the power supply was turned on to connect the voltage. The spinning voltage was adjusted to 15kV, the spinning distance was 9cm, the spinning speed was 1.5ml / h, and the spinning time was 8h to obtain nanofibers. The diameter of the nanofibers was about 400nm-600nm, and the pore size of the holes on the surface of the nanofibers was about 30nm-50nm.
[0106] Figure 1 This is a morphology picture of the lauric acid glyceryl ester-PMMA nanofibers prepared in this example.
[0107] like Figure 1 There are many tiny holes on the fiber surface, which are helpful for the release of antibacterial substances.
[0108] Example 2
[0109] The difference between this embodiment and embodiment 1 is that the added amounts of laurin and PMMA powder are different, specifically: the mass ratio of laurin to PMMA powder is (1:1).
[0110] Example 3
[0111] The difference between this embodiment and embodiment 1 is that the electrospinning process parameters are different, specifically: the nanofibers are obtained under the conditions of 20 kV spinning voltage, 13 cm spinning distance, 2 ml / h spinning speed, and 8 h spinning time. The diameter of the obtained nanofibers is about 200 nm-400 nm, and the pore size of the nanofiber surface is about 10 nm-30 nm.
[0112] Example 4
[0113] A bone cement formula, powder: PMMA: 74%, BPO: 2.0%, lauric acid monoglyceride-PMMA nanofiber of Example 1: 14%, BaSO4: 10%;
[0114] Liquid: MMA: 98.0%, DMPT: 1.99%, HQ: 100ppm.
[0115] The liquid-to-solid ratio of powder and liquid is 1ml:2g.
[0116] Example 5
[0117] A bone cement formula, powder: PMMA: 72%, BPO: 2.0%, lauric acid monoglyceride-PMMA nanofiber of Example 1: 16%, BaSO4: 10%;
[0118] Liquid: MMA: 98.0%, DMPT: 1.99%, HQ: 100ppm.
[0119] The liquid-to-solid ratio of powder and liquid is 1ml:2g.
[0120] Example 6
[0121] A bone cement formula, powder: PMMA: 76%, BPO: 2.0%, lauric acid monoglyceride-PMMA nanofiber of Example 1: 12%, BaSO4: 10%;
[0122] Liquid: MMA: 98.0%, DMPT: 1.99%, HQ: 100ppm.
[0123] The liquid-to-solid ratio of powder and liquid is 1ml:2g.
[0124] Example 7
[0125] A bone cement formula, powder: PMMA: 74%, BPO: 2.0%, lauric acid monoglyceride-PMMA nanofiber of Example 2: 14%, BaSO4: 10%;
[0126] Liquid: MMA: 99%, DMPT: 0.99%, HQ: 100ppm.
[0127] The liquid-to-solid ratio of powder and liquid is 1ml:2g.
[0128] Example 8
[0129] A bone cement formula, powder: PMMA: 74%, BPO: 2.0%, lauric acid monoglyceride-PMMA nanofiber of Example 3: 14%, BaSO4: 10%;
[0130] Liquid: MMA: 98.5%, DMPT: 1.49%, HQ: 100ppm.
[0131] The liquid-to-solid ratio of powder and liquid is 1ml:2g.
[0132] Comparative Example 1: Traditional bone cement (without nanofibers)
[0133] Bone cement formula, powder and liquid; the liquid-to-solid ratio of powder and liquid is 1ml:2g.
[0134] In terms of mass percentage, the powder includes the following components: PMMA 88%, BPO 2.0% and BaSO4 10%;
[0135] According to mass concentration, the liquid includes the following components: MMA 98%, DMPT 1.99%, HQ 100 ppm.
[0136] Comparative Example 2
[0137] The difference between this comparative example and Example 4 is that the monolaurin-PMMA nanofibers are replaced with vancomycin, and the content remains unchanged.
[0138] Test Example 1 Antibacterial Rate Detection
[0139] (I) Test samples:
[0140] Bone cement was prepared according to the bone cement formula of Example 4 and Comparative Example 2: the obtained nanofibers were shredded and mixed with bone cement powder, and the powder was mixed with bone cement liquid to prepare bone cement.
[0141] (II) Test methods and results:
[0142] Laurin has inhibitory effects on both Gram-positive and Gram-negative bacteria, and is highly sensitive to Staphylococcus aureus, Bacillus subtilis and Escherichia coli. The inhibition rate of bone cement against Staphylococcus aureus was measured by the agar plate dilution method.
[0143] (1) Bacteria culture:
[0144] Place multiple layers of medical gauze in the culture dish, sterilize with high temperature and wet heat, and then dry. Perform the test operation on a sterile operating table: Pipette 10mL of PBS buffer onto the gauze to ensure the humidity environment in the culture dish, place the prepared bone cement specimens on the gauze (3 specimens of each type as parallel controls), and pipette 10μL of the prepared Staphylococcus aureus liquid on the surface of each specimen and apply it evenly. Place the culture dish with the liquid applied in a 37℃ incubator for 24h.
[0145] (2) Determination of Staphylococcus aureus concentration on the surface of the specimen:
[0146] After 24 hours of incubation, the specimens were taken out individually and placed in 1 mL of PBS buffer and shaken with a vortex mixer for 3 minutes to allow the Staphylococcus aureus on the surface of the resin sheet to fall off and disperse into the solution. The specimens were then diluted step by step, and the plates with the same dilution multiples were photographed.
[0147] The measured antibacterial rate was compared with the antibacterial rate of bone cement with added antibiotics. The results showed that the antibacterial rate of bone cement with added laurin was still above 90% after 72 hours, while the antibacterial rate of bone cement with added antibiotic-vancomycin was around 80% after 72 hours.
[0148] Figure 2 This is the test result of bone cement antibacterial rate in this test case.
[0149] like Figure 2 This indicates that the addition of this antibacterial agent has a better antibacterial effect.
[0150] Test Example 2 Mechanical Properties Test
[0151] (I) Test samples: Bone cement prepared by the bone cement formula of each embodiment and comparative example: the obtained nanofibers are chopped and mixed with bone cement powder, and the nanofibers are mixed with bone cement liquid to prepare bone cement.
[0152] (II) Test the mechanical properties of bone cement. Specific test methods:
[0153] Compression strength test: Mix a set of bone cement powder and liquid under (23±1)℃ environment. When the mixed bone cement is in dough form, carefully fill it into a specific mold to prepare a 6×12mm sample column. Place the test sample on the static compression test device of the test equipment, start the test machine to apply load to the sample at a constant crosshead rate within the range of 19.8mm / min-25.6mm / min, and stop when the sample breaks or has passed the upper yield point.
[0154] Bending strength test: Mix a set of bone cement powder and liquid under (23±1)℃ environment. When the mixed bone cement is in dough form, carefully fill it into a specific mold to prepare a 75×10×3.3mm specimen. Place the test specimen on the test equipment, use a bending tester to apply force on the central load column from zero at a crosshead rate of 5mm / min±1mm / min, record the change of the specimen deflection with the applied force, and continue to apply force until the specimen breaks.
[0155] (III) Test results: See Table 1.
[0156] Table 1
[0157] sample Compressive strength(MPa) Flexural strength(MPa) Example 4 84.25±3.73 59.42±2.13 Example 5 83.82±3.37 58.75±2.42 Example 6 84.77±2.19 58.37±2.52 Example 7 85.02±3.12 58.14±2.18 Example 8 84.83±2.94 59.38±2.31 Comparative Example 1 84.47±2.48 58.29±2.13 Comparative Example 2 85.44±2.15 58.72±2.42
[0158] The mechanical properties test results show that the mechanical properties of the bone cement prepared using the antibacterial nanofibers of the present application (Examples 4 to 8) are not significantly different from those of the existing bone cement (Comparative Example 1) (p>0.05), proving that the introduction of antibacterial nanofibers has no significant effect on the mechanical properties of bone cement.
[0159] In summary, the present invention adopts laurin-PMMA nanofibers as antibacterial substances, and uses electrospinning to blend them with PMMA copolymers to prepare nanofibers to prepare antibacterial bone cement. While the amount of antibacterial substance added is increased, the mechanical properties of the bone cement can be ensured to remain unchanged, and the porous structure on the surface of the nanofibers can improve the antibacterial properties of the bone cement.
[0160] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A bone cement with antibacterial properties, characterized in that: It comprises a solid phase component and a liquid phase component; the solid phase component comprises, by mass percentage, 70-78% of PMMA, 1.5-2.0% of initiator, 12-16% of lauric acid glyceryl ester-PMMA nanofibers and 8-12% of developer; The liquid phase components include, by mass concentration, 98-99% MMA, 1.0-2.0% accelerator, and 100±10 ppm inhibitor.
2. The antibacterial bone cement according to claim 1, characterized in that: The diameter of the laurin-PMMA nanofiber is 200nm-600nm; the diameter of the holes on the surface of the laurin-PMMA nanofiber is 10-50nm.
3. The antibacterial bone cement according to claim 1 or 2, characterized in that: The preparation method of the lauric acid glyceride-PMMA nanofiber comprises: The mixed solution of lauric acid glyceryl ester and PMMA copolymer was electrospun to form fibers.
4. The antibacterial bone cement according to claim 3, characterized in that: The laurin includes at least one of monolaurin and dilaurin.
5. A method for preparing the antibacterial bone cement according to any one of claims 1 to 4, characterized in that: The following steps are involved: (a) providing laurin-PMMA nanofibers; (b) chopping the lauric acid glyceryl ester-PMMA nanofibers and mixing them with PMMA, an initiator and a developer to obtain a solid phase component; (c) mixing MMA, a promoter and an inhibitor to obtain a liquid phase component; (d) The solid phase component and the liquid phase component constitute the bone cement with antibacterial properties.
6. The preparation method according to claim 5, characterized in that: Step (a) The method for preparing laurin-PMMA nanofibers comprises: The mixed solution of lauric acid glyceryl ester and PMMA copolymer was electrospun to form fibers.
7. The preparation method according to claim 6, characterized in that: The mass ratio of lauric acid glyceryl and PMMA copolymer in the mixed solution of lauric acid glyceryl and PMMA copolymer is 0.5-1:1; Preferably, the number average molecular weight of PMMA polymer is 1×10 5 -5×10 5 .
8. The preparation method according to claim 6, characterized in that: The solvent used for the mixed solution of lauric acid glyceryl and PMMA copolymer is a mixed solvent of dichloromethane and trifluoroacetic acid; Preferably, the volume ratio of dichloromethane to trifluoroacetic acid is 2:1-2.
9. The preparation method according to claim 6, characterized in that: The total concentration of laurin and PMMA copolymer in the mixed solution of laurin and PMMA copolymer is 15-20 wt %.
10. The preparation method according to any one of claims 6 to 9, characterized in that: The process parameters of electrospinning include at least one of the following conditions: Spinning voltage: 15-20kv; Spinning speed: 1.5-2ml / h; Spinning distance: 9-13cm; Receiving substrate: PET.